Budd-Chiari syndrome in children and adolescents therapeutic radiological intervention - Wang, Lei (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2013)
OBJECTIVE: Due to its minimal-invasive approach, endovascular procedure had replaced surgery in treating Budd-Chiari syndrome (BCS). The interventional therapy was a safe and effective treatment in adults with BCS and the cure rate was high. However Budd-Chiari syndrome in children and adolescents is rare. Published literature on interventional procedure for Budd-Chiari syndrome in children and adolescents is scarce. The aim of the study was to present results of percutaneous transluminal angioplasty (PTA) and stents placement in children and adolescents with BCS and to evaluate the efficacy and safety in these patients of this approach